Analysis of Fiber Fractions in Corn Cobs Fermented with Phanerochaete chrysosporium Supplemented with Different Carbohydrate Sources - Afdal, M; Astuti, Tri; Sari, Rica Mega (Department of Agriculture, 2024)
This study aimed to evaluate the content of Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), cellulose, and hemicellulose in corn cobs fermented with white rot fungi (Phanerochaete chrysosporium) and supplemented with various carbohydrate sources. A Completely Randomized Design was employed, consisting of four treatments with four replications each. The results revealed the highest NDF content in T3 (80.16%), followed by T2 (79.50%), T0 (77.30%), and T1 (73.63%). The highest ADF content was observed in T1 (47.08%), T0 (45.78%), T3 (44.85%), and T2 (43.13%). The highest cellulose content was recorded in T2 (17.51%), followed by T1 (15.32%), T0 (15.32%), and T3 (13.39%). For hemicellulose, the highest values were found in T2 (36.37%), followed by T3 (35.30%), T0 (31.51%), and T1 (26.54%). It can be concluded that fermenting corn cobs with P. chrysosporium and supplementing with different carbohydrate sources significantly (P<0.01) affected the fiber fractions (NDF, ADF, cellulose, and hemicellulose). Rice bran (T1) was most effective in reducing NDF and hemicellulose content, molasses (T2) in reducing ADF content, and tapioca flour (T3) in lowering cellulose content.